FRI0293 Characteristics of Patients with Rheumatoid Arthritis Treated with Biologic Therapy as Monotherapy. (10th June 2014) - Gόmez-Centeno, A.; Martínez, O.; Ballina, F.; Rodriguez, J.; Graña, J.; Brito, M.; Sampedro, J.; Iglesias, G.; Delgado, C.; Monteagudo, I.
Abstract : Background: The treatment for Rheumatoid Arthritis (RA) is based mainly on the use of synthetic or biological DMARDs. Most current guidelines recommend the use of biologics in combination with MTX as this combination shows better control of radiological disease progression. However several studies have shown that up to 30% of patients are treated with biologic monotherapy for different reasons. Objectives: The aim of the study was to know the characteristics of patients receiving biologic monotherapy, including the previous treatment received and the reasons why they changed treatment. Methods: Observational, cross-sectional, retrospective and multicentric study with the participation of 38 rheumatology units in Spain. Patients were consecutively included if they were >18, with moderate to severe RA with an inadequate response or intolerance to synthetic or biologic DMARDs (as recommended by the Spanish Rheumatology Society, SER), treated with biologic DMARDs in monotherapy for >6 months and gave informed consent. Collected variables included sociodemographic (age, gender), clinical (RA diagnosis date, extra-articular manifestations, DAS28, CDAI, and SDAI indexes, presence of joint damage), and treatment (prior treatment with DMARDs and reasons for change to biologics as monotherapy). Results: Two hundred and nine patients were included, 82.8% were women, mean (SD) age was 57.6 (13.6). Mean (SD) time since RA diagnosis was 13.5 (8.8) years. Most had RF (59.8%), 38.3% anti-CCP antibodies, 73.7% joint damage; 28.5% had extra-articular manifestations. At the study visit, 58.4% of patients were receiving tocilizumab, 18.7% etanercept, 12.4% adalimumab, and 10.5% other biologics. Mean (SD) number of tender joints was 1.9 (3.0), of swollen joints was 0.84 (2.1); mean (SD) CRP level was 4.0 (7.7), and ESR was 14.6 (13.4). Mean (SD) DAS28 score was 2.7 (1.1), CDAI index was 8.4 (6.9), and SDAI index was 8.8 (7.1), with 49.8%, 15.8%, and 20.1% of patients on in remission, respectively. The first synthetic DMARD prescribed was MTX for 62.3% of patients, followed by gold salts (17.9% of patients). Mean time (months) since first DMARD prescription was 19.5 (52.8) [mean (SD)] and 89.8 (86.4) since the first biologic use. Patients had received a mean (SD) of 2.6 (1.4) synthetic DMARDs and 1.7 (0.9) biologics. Just before initiating monotherapy, 45.5% of patients had received synthetic+biologic DMARD, 30.6% synthetic DMARD as monotherapy, and 23.9% another biologic as monotherapy (30.0% adalimumab and 28.0% etanercept). The most frequent reasons for treatment withdrawal before monotherapy were lack of effectiveness (61.2%), intolerance (10.5%), adverse events (10.0%), and lack of adherence (1.5%). Conclusions: Patients with RA treated with biologic DMARDs as monotherapy had previously received more than two synthetic DMARDs. The clinical control with biologics as monotherapy was good, with a mean DAS28 of 2.7. The withdrawal of the synthetic DMARD was mainly due to lack of effectiveness, intolerance, or adverse event. Treatment with biologics as monotherapy is a therapeutic alternative for patients who do not tolerate or cannot receive synthetic DMARDs. Disclosure of Interest: A. Gόmez-Centeno Grant/research support: Pfizer, Abbvie, Menarini, Roche, Amgen, MSD. Study funded by Roche Farma SA, Consultant for: UCB, Boehringer Ingelheim, Roche, Abbvie, Pfizer, Speakers bureau: Pfizer, Roche, Abbvie, MSD, UCB, Menarini, O. Martínez: None declared, F. Ballina: None declared, J. Rodriguez: None declared, J. Graña: None declared, M. Brito: None declared, J. Sampedro: None declared, G. Iglesias: None declared, C. Delgado: None declared, I. Monteagudo: None declared DOI: 10.1136/annrheumdis-2014-eular.4913